1989
DOI: 10.2527/jas1989.67112930x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Beta-Adrenergic Agonists on Porcine Adipocyte Metabolism In Vitro3

Abstract: Backfat was obtained at slaughter from market weight hogs to study the acute effects of clenbuterol (CB), ractopamine (RAC) or epinephrine (EPI), in the presence and absence of theophylline (THEO) or adenosine deaminase (ADA), on rates of lipolysis and fatty acid synthesis in vitro. Only EPI increased lipolytic rate in the absence of THEO or ADA. In the presence of THEO or ADA, RAC and CB were lipolytic, although CB had a lower maximal response. With THEO present, RAC and EPI increased lipolysis with a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…In this study, β-adrenergic stimulation by clenbuterol led to in- creased basal lipolysis and a modest decrease of adipogenesis in adipocytes. This result is consistent with the report showing lipolysis is more sensitive to beta-adrenergic stimulation than is lipogenesis [21]. Beta receptors are linked to Gs proteins, which are in turn linked to adenyl cyclase.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, β-adrenergic stimulation by clenbuterol led to in- creased basal lipolysis and a modest decrease of adipogenesis in adipocytes. This result is consistent with the report showing lipolysis is more sensitive to beta-adrenergic stimulation than is lipogenesis [21]. Beta receptors are linked to Gs proteins, which are in turn linked to adenyl cyclase.…”
Section: Discussionsupporting
confidence: 93%
“…Adipocytes were isolated from the subcutaneous fat depot of male castrate pigs weighing ϳ100 kg by collagenase digestion as described previously (19,27,28). Briefly, the isolated cells were diluted to approximate 20% cell suspensions with DMEM (Sigma, St. Louis, MO) containing 3% fatty acid-free serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Nourozi et al (2008) did not observe significant effect on blood glucose and urea contents for ewes with terbutaline and metaproterenol added to the diet. However, Liu et al (1989), and Peterla and Scanes (1990) reported that β-AA such isoproterenol, cimaterol, clenbuterol and ractopamine, have direct effects on porcine adipose tissue in vitro, all decreasing lipogenesis and inhibiting lipid synthesis. Beermann (1987) mentioned that blood metabolites such as plasma free fatty acids and glucose increased sharply after administration of cimaterol, within the first 4to 10 h to then got back to baseline levels, consistent with an acute lipolytic and hyperglycemic effect of β-AA.…”
Section: Serum Metabolitesmentioning
confidence: 96%